Aerobic Exercise Overcomes the Age-Related Insulin Resistance of Muscle Protein Metabolism by Improving Endothelial Function and Akt/Mammalian Target of Rapamycin Signaling - Fujita, Satoshi; Rasmussen, Blake B.; Cadenas, Jerson G.; Drummond, Micah J.; Glynn, Erin L.; Sattler, Fred R.; Volpi, Elena (Diabetes (New York, N.Y.), 2007)
Aerobic Exercise Overcomes the Age-Related Insulin Resistance of Muscle Protein Metabolism by Improving Endothelial Function and Akt/Mammalian Target of Rapamycin Signaling Satoshi Fujita 1 2 , Blake B. Rasmussen 3 4 , Jerson G. Cadenas 1 2 , Micah J. Drummond 3 , Erin L. Glynn 3 , Fred R. Sattler 2 and Elena Volpi 1 2 1 Department of Internal Medicine, University of Texas Medical Branch, Galveston, Texas 2 Department Medicine, University of Southern California, Los Angeles, California 3 Department of Physical Therapy, University of Texas Medical Branch, Galveston, Texas 4 Department of Kinesiology and Biological Sciences, University of Southern California, Los Angeles, California Address correspondence and reprint requests to Elena Volpi, MD, PhD, Division of Geriatric Medicine and Sealy Center on Aging, University of Texas Medical Branch, 301 University Blvd., Galveston, TX 77555-0460. E-mail: evolpiatutmb.edu Abstract Muscle protein metabolism is resistant to insulin's anabolic effect in healthy older subjects. This is associated with reduced insulin vasodilation. We hypothesized that aerobic exercise restores muscle protein anabolism in response to insulin by improving vasodilation in older subjects. We measured blood flow, endothelin-1, Akt/mammalian target of rapamycin (mTOR) signaling, and muscle protein kinetics in response to physiological local hyperinsulinemia in two groups of older subjects following a bout of aerobic exercise (EX group: aged 70 ± 2 years; 45-min treadmill walk, 70% heart rate max) or rest (CTRL group: aged 68 ± 1 years). Baseline endothelin-1 was lower and blood flow tended to be higher in the EX group, but protein kinetics was not different between groups. Insulin decreased endothelin-1 ( P < 0.05) in both groups, but endothelin-1 remained higher in the CTRL group ( P < 0.05) and blood flow increased only in the EX group (EX group: 3.8 ± 0.7 to 5.3 ± 0.8; CTRL group: 2.5 ± 0.2 to 2.6 ± 0.2 ml · min −1 · 100 ml leg −1 ). Insulin improved Akt phosphorylation in the EX group and increased mTOR/S6 kinase 1 phosphorylation and muscle protein synthesis (EX group: 49 ± 11 to 89 ± 23; CTRL group: 58 ± 8 to 57 ± 12 nmol · min −1 · 100 ml leg −1 ) in the EX group only ( P < 0.05). Because breakdown did not change, net muscle protein balance became positive only in the EX group ( P < 0.05). In conclusion, a bout of aerobic exercise restores the anabolic response of muscle proteins to insulin by improving endothelial function and Akt/mTOR signaling in older subjects. 4EBP1, 4E-binding protein 1 FSR, fractional synthetic rate ICG, indocyanine green mTOR, mammalian target of rapamycin S6K1, S6 kinase 1 Footnotes Published ahead of print at http://diabetes.diabetesjournals.org on 9 March 2007. DOI: 10.2337/db06-1566. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted March 1, 2007. Received November 9, 2006. DIABETES